The Effectiveness of Using Digital School Applications in Management of Online Civics Learning - Luthfina Riska Aprilia; Nani Mediatati (Universitas Pahlawan Tuanku Tambusai, 2022)
Covid-19 has hit the whole world, even Indonesia, which requires to be online learning. Schools need facilities to support online learning. This research aims to describe the effectiveness of digital school applications in the management of online learning. This research is a qualitative descriptive study in which the technique data collection uses 3 techniques, the first is observation, the second is interviews with 1 teacher PPKn, and the third is distributed questionnaires to 36 students of class X TSM 1. Data analysis techniques carried out by means of data reduction, data presentation, and conclusions. Based on the research results, digital schools are effective in managing online learning in class X TSM 1. Digital schools effective because it contains six aspects, namely information quality, system quality, service quality, level of use, user satisfaction, and benefits obtained. The results of the questionnaire show that the 6 aspects obtained an average of 78.17%. With the fulfillment of the aspects therefore, digital schools are effectively used as a means that can support online learning.